2022
DOI: 10.3389/fpubh.2021.785602
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Patient's Refusal of Recommended Cancer Surgery: Based on Surveillance, Epidemiology, and End Results

Abstract: ObjectivesMost non-metastatic cancer patients can harvest a preferable survival after surgical treatment, however, patients sometimes refuse the recommended cancer-directed surgery. It is necessary to uncover the factors associated with patent's decision in taking cancer surgery and explore racial/ethnic disparities in surgery refusal.MethodsBased on the Surveillance, Epidemiology and End Results (SEER)-18 program, we extracted data of non-metastatic cancer patients who didn't undergo surgery. Ten common solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 23 publications
(33 reference statements)
6
12
0
Order By: Relevance
“…Non-Hispanic Blacks were more likely to refuse getting surgery as recommended for breast cancer compared to Non-Hispanic Whites. This is consistent with similar studies that have assessed the predictors of breast cancer-recommended surgery refusal [7,[14][15][16][17][18][19]. This finding can be attributed to low socioeconomic status (SES) and distrust of health care among racial minorities [7,27,29].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Non-Hispanic Blacks were more likely to refuse getting surgery as recommended for breast cancer compared to Non-Hispanic Whites. This is consistent with similar studies that have assessed the predictors of breast cancer-recommended surgery refusal [7,[14][15][16][17][18][19]. This finding can be attributed to low socioeconomic status (SES) and distrust of health care among racial minorities [7,27,29].…”
Section: Discussionsupporting
confidence: 88%
“…Increasing age was also significantly associated with an increased odds of refusing recommended surgery being performed, which was disproportionate for women aged 80 years and older compared to those aged 40-49 years consistent with other studies on the topic [7,[14][15][16][17][18][19]. Advanced age is associated with an increased risk for comorbidities and decreased survival after cancer treatment [4,31].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Cancer is one of the most fatal diseases and leading causes of human death around the world, and its prevention remains a serious issue [ 1 ]. Due to the inefficient sensitivity, specificity, and resolution of traditional diagnostic modalities, early-stage tumors, especially tiny lesions, cannot be effectively detected [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Post-surgery patients may develop declining psychosocial functioning with respect to their quality of life, cancer-related distress, sexual dysfunction, body image dysmorphism, anxiety, and depression, hence affecting surgery refusal rates [7,[11][12][13]. Previous studies have also found age, race, marital status, and income level to be associated with surgery refusal, with NH Black patients being less likely to receive breast cancer surgical treatment [7,[14][15][16][17][18][19]. However, these studies focused on data prior to 2014.…”
Section: Introductionmentioning
confidence: 99%